2014
DOI: 10.1186/1471-2466-14-17
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation reduces energy expenditure in amyotrophic lateral sclerosis

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) leads to chronic respiratory failure. Diaphragmatic dysfunction, a major driver of dyspnea and mortality, is associated with a shift of the burden of ventilation to extradiaphragmatic inspiratory muscles, including neck muscles. Besides, energy expenditure is often abnormally high in ALS, and this is associated with a negative prognostic value. We hypothesized that noninvasive ventilation (NIV) would relieve inspiratory neck muscles and reduce resting energy expend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 41 publications
2
31
1
Order By: Relevance
“…The higher BMI despite lower energy intake in the more advanced‐stage patients with macroglossia may indicate abnormal central metabolic regulation and an energy imbalance. Macroglossia in advanced ALS may be a result of overfeeding and replacement of the tongue muscle by fat under conditions of extremely low energy expenditure …”
Section: Discussionmentioning
confidence: 99%
“…The higher BMI despite lower energy intake in the more advanced‐stage patients with macroglossia may indicate abnormal central metabolic regulation and an energy imbalance. Macroglossia in advanced ALS may be a result of overfeeding and replacement of the tongue muscle by fat under conditions of extremely low energy expenditure …”
Section: Discussionmentioning
confidence: 99%
“…Recent physiological studies have further refined our knowledge of the benefit of NIV in ALS. By resting accessory muscles, NIV allows a dramatic reduction of energy expenditure (−7% of daily resting energy expenditure), as well as ‘cortical resting’ via decreased premotor cortex activity …”
Section: Beneficial Effects Of Nivmentioning
confidence: 99%
“…This approach was initially proposed in Duchenne's myopathy in 1994, before being ceased following demonstration of excess mortality in the ‘early NIV’ group . However, several arguments suggest that early ventilation could reduce the respiratory decline in ALS and decrease respiratory work . A large retrospective study and three small series have demonstrated an improvement in survival for patients initiating NIV with VC > 80% predicted, although this effect was not confirmed when sham NIV was used in the control group .…”
Section: Criteria For Initiation Of Nivmentioning
confidence: 99%
“…Conversely, NIV may positively affect energy balance [28], with a possible protective effect on peripheral muscle mass.…”
Section: Nutritional Status and Respiratory Functionmentioning
confidence: 99%
“…A recent study of 10 patients with ALS who had signs of respiratory failure and diaphragmatic dysfunction showed that although resting energy expenditure was below predicted values while breathing spontaneously, noninvasive ventilation (NIV) induced a further median decrease of resting energy expenditure by 7%. The transfer of the respiratory burden from the diaphragm to the accessory inspiratory muscles may be a potent contributor to weight loss, reversible by NIV [28].…”
Section: Nutritional Status and Respiratory Functionmentioning
confidence: 99%